한국어 구어적 종결 표현 교육 연구 - 종결기능 연결어미를 중심으로 - 손마정(Ma Jeong Son) (한국어문화교육, 2014)
【벼리】한국어 구어는 문어와 다른 여러 가지 특징을 가진다. 그 중 하나는 종결어미가 아닌 요소들에 의해 종결되는 문장이 많다는 것이 고, 그 중에서도 연결어미로 문장이 끝나는 경우가 자주 나타난다. 한 국어 학습자들이 한국어로 의사소통을 하게 되면 이러한 부분에서 어 려움을 느낄 수 있다. 본고에서는 현행 한국어 교육에서 이에 대한 교육이 어떻게 이루어지 고 있는지를 한국어 회화 교재를 통해 점검해볼 것이다. 그리고 한국 어 모어 화자와 한국인 학습자들의 실제 발화에서 연결어미에 의해 종 결되는 문장의 빈도와 양상을 살핀 후 비교하여, 교육이 필요하다고 생각되는 부분에 대해 교육 방안을 제시해보고자 한다. In Korean, types of sentences are determined by endings. Therefore, it is crucial to educate usages of endings in learning Korean. Among them, Final endings are used to terminate sentences in Korean. But in colloquial Korean, connective endings are often used to finish sentences. Previous studies suggest that some connective endings such as ‘-거 든’, ‘-고’, ‘-는데’, ‘-니까’, ‘-다고’, ‘-려고’, and ‘-어서’ are most frequently employed to end sentences. They are called 'connective endings functioning as final endings'. This study analyzes several textbooks for teaching colloquial Korean in order to examine how those connective endings are educated. Most textbooks, those endings are presented as final endings without any detailed explanation after the indication of their usages as connective. Furthermore, enough practice is not given, either. In contrast to the previous studies, This study analyzes Korean spoken sentences on talk shows, and presents a list of connective endings that are used to end sentence. As a results, ‘-(으)면’ and ‘-아/어가지고’ are appeared more frequently than ‘-려고’ in final sentence positions. However, Korean learners do not use ‘-거든’ and ‘-아/어가지고’ in spoken Korean. They use ‘-(으)면' in similar frequency as native speakers do. Even though its types of usages are very limited. Based on this observations, this study presents education methods of ‘-거든’, ‘-(으)면’ and ‘-아/어가지고’.